2022
DOI: 10.1108/jhtt-11-2022-332
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: TheJournal of Hospitality and Tourism Technology(JHTT): a retrospective review using bibliometric analysis

Abstract: IntroductionInformation and communication technologies are an integral part of the hospitality and tourism field. By transforming industry practices, strategies and structures, information and communication technologies have been renovating the tourism sector since the 1980s (Porter, 2001;Bulchand-Gidumal et al., 2011). In addition, new technologies have been aiding in creating new business models in the hospitality and tourism business. Consumers presently rely on online consumer-produced content while making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…To achieve the objectives set in this research, a bibliometric analysis was conducted using VOSViewer. In addition, a systematic literature review was conducted as the bibliometric analysis alone is considered insufficient to explore and further the research practices in the field (Ali et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To achieve the objectives set in this research, a bibliometric analysis was conducted using VOSViewer. In addition, a systematic literature review was conducted as the bibliometric analysis alone is considered insufficient to explore and further the research practices in the field (Ali et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Restaurants leverage knowledge for competitive advantage through creative product development models, technological uniqueness and cost-of-sales efficiencies (Ali et al, 2022a(Ali et al, , 2022b. Relational ties facilitate external knowledge acquisition in crucial customer relationships (Hoang et al, 2023).…”
Section: Product Development Efficiency Of Restaurantsmentioning
confidence: 99%
“…Research in the field of hospitality and tourism utilising this technique can be broken down into several distinct areas, such as by country, by specific topic or by publication source. For instance, Ali et al (2022) found that publication and citation matrixes showed that the Journal of Hospitality and Tourism Technologies (JHTT) has grown in productivity and impact. Also, empirical and quantitative research designs dominate the JHTT corpus.…”
Section: Related Literaturementioning
confidence: 99%
“…For instance, Ali et al (2022) found that publication and citation matrixes showed that the Journal of Hospitality and Tourism Technologies (JHTT) has grown in productivity and impact. Also, empirical and quantitative research designs dominate the JHTT corpus.…”
Section: Related Literaturementioning
confidence: 99%